KEKUATAN EKSEKUTORIAL SURAT PENGAKUAN UTANG DIBAWAH TANGAN DALAM PINJAM MEMINJAM UANG DENGAN JAMINAN HAK ATAS TANAH: STUDI PUTUSAN NOMOR: 2661 K/PDT./2022 - Khoiriah Pane, Melyda; Siregar, Mahmul; Mulhadi, Mulhadi (Penerbit Lafadz Jaya, 2025)
This study aims to analyze the validity and executorial power of debt acknowledgment letters made privately (non-notarial) in money lending agreements with land rights as collateral, using the Supreme Court Decision No. 2661 K/Pdt/2022 as a case study. Privately made debt acknowledgment letters are often used due to their simplicity, yet they pose legal issues when the debtor defaults and collateral execution is needed. The research employs a normative juridical method with statutory and case approaches. It is based on legal certainty theory, legal protection theory, and justice theory. The findings show that privately made debt acknowledgment letters do not have direct executorial power without notarial authentication or formal registration of collateral rights. Nevertheless, such letters can still serve as admissible evidence in breach of contract lawsuits. The Supreme Court's decision in this case highlights the importance of legal protection and certainty in private law agreements. The study recommends using notarial deeds for debt acknowledgment to ensure executorial strength and legal safeguards for the parties involved.